Edukacja jako przestrzeń rozwoju podmiotowości jednostki - Anna Sokolnicka (Nicolaus Copernicus University in Toruń, 2009)
A man in XXI century is too often being made by society just as a consumer of goods   and pop-culture. In educational practice there is usually also more important to have than   to be. That is why is so necessary to consider the meaning, which education could have   today. The author (of this article) thinks, that it should be the space of individual's personality   development. For make this situation possible we must respect those pedagogical   cathegories like: dialogue, empowerment, sociological ambivalence or borderlands. That   is the only way for making education more human and more useful for everyone. Lastly   we must notice that in such matter, asking question might be more difficult but also more   essential than reply to them.   36